Dynamic Motion Analysis Using a Wearable Sensor System in a Stabilometer Installed with Generation Function of Disturbance from a Floor - Yasuhiro Nakamichi; Nobutaka Tsujiuchi; Akihito Ito; Kiyoshi Hirose; Akiko Kondo (Proceedings, 2020)
In this study, we developed an evaluation method using posture and joint torque for the evaluation of balance ability. The evaluation and analysis of standing with a disturbance is conducted for effective balance evaluations. Center of pressure information is mainly used for the evaluation of balance ability using a stabilometer. It is necessary for a more detailed analysis to combine the measurements of body motion. The analysis of posture and joint angle is conducted by body-motion measurement, and joint torque is calculated using ground reaction force and posture information. In this study, we estimated posture and joint torque using a wearable sensor system in the balance evaluation of standing using a stabilometer that generates a disturbance. The analytical results indicated the posture information and joint torque. Analysis and feedback in a short time can be conducted using the wearable sensor system.